Non-infectious Health Risks of Young Adults Serving in International Volunteer Services - Thomas Küpper; K. Neppach; J. Martin; Travis Heggie; B. Rieke (University of Applied Sciences in Tarnow, Poland, 2020)
Introduction: Young people serving as volunteers in international projects show a different risk profile to "normal" travellers. Data are scarce. While infectious risks were published elsewhere we focus now on non-infectious risks. Material and methods: 153 questionnaires, obtained from volunteers returning from their project were evaluated. Questions included age, situation abroad (living space and work), travel experience, region of the project, language skills, pre-travel advise, type of problems abroad (accidents, traffic, violence, robbery, sexual assault, psychosocial stress etc.). Results: Several factors, normally not included in pre-travel advice, cause significant psychosocial stress which decreases a bit during the stay. Special problems are insufficient language skills, (subjective) safety at night, traffic / transport, and violence. Psychosocial stress was the most important reason to stop the activity and to return home ahead of schedule (4% of all volunteers). Conclusions: Pre-travel advice of young volunteers should include psychosocial factors and other topics additional to infectious diseases, vaccination, and hygiene. Sufficient training in common but minor medical problems (headache, sunburn, minor wounds) is a "must". A comprehensive advice and training may need two days and may be realized in groups of 5 to 12 participants. Health and safety should become a more important topic of all projects.